Analisis Keefektifan Implementasi Game Based Learning dalam Meningkatkan Pemahaman Siswa Materi Sistem Tata Surya - Indri Rahayu Septiani; Enjang Yusuf Ali; Ali Ismail (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research discusses the impact of the model chosen by the teacher on students' understanding during the learning process. The effectiveness of the model used also determines the success of the learning process. Based on observations in class IV of Sukasari Elementary School in June 2023, researchers found problems in the learning mechanism that had a negative effect on students' understanding results. This problem is caused by the lack of effectiveness of conventional learning models which are teacher-centered, less varied and uninteresting. Therefore, researchers recommend Game Based Learning as an alternative to traditional teaching to improve students' understanding of the material. The target of this research is to analyze the effectiveness of Game Based Learning in increasing students' understanding of the concept of solar system material in class VI SDN Sukasari by research using the quasi experimental design method with a two group pre-test-post-test design. The results of the research show that the application of Game Based Learning in schools is effective in increasing students' understanding of the concept of solar system material. The effect is classified as moderate with the N-gain value in the experimental class using Game Based Learning at Sukasari Elementary School being 0.6357 and the n-gain percent being 0.6357. 63.5659%. The effectiveness of the n-gain score is classified as moderate because it is higher than 0.30 and lower than 0.70. Therefore, this research proves that the application of Game Based Learning in schools is effective in increasing students' understanding of the concept of solar system material.